2012
DOI: 10.17221/107/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of flaxseed for lignan determination by gas chromatography-mass spectrometry method

Abstract: Sarajlija H., Čukelj N., Novotni D., Mršić G., Brnčić M., Ćurić D. (2012): Preparation of flaxseed for lignan determination by gas chromatography-mass spectrometry method. Czech J. Food Sci., 30: 45-52.Since 1980s, several methods for the determination of lignans in food samples have been developed depending on the types of lignans and foods analysed, but mostly on flaxseed as a reference food. In this work, specific steps in flaxseed preparation for lignan secoisolariciresinol analysis by gas chromatography-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Hosseinian and Beta () also reported that sodium hydroxide or calcium hydroxides are the prominent bases which are employed for liberating SDG. Direct acid hydrolysis of milled flaxseed also reported a higher concentration of secoisolariciresinol (8,566 ± 169 μg/g, 8,571 ± 192 μg/g, respectively) from defatted and full fat flaxseed in comparison to the method in which ethanolic extraction was applied before the acid hydrolysis step which yielded 5,172 ± 49 μg/g and 5,159 ± 83 μg/g, respectively (Sarajlija et al, ). A high level of purity (95%) of SDG was obtained in the process of extraction where the defatting of flaxseed powder was done by pilot‐scale supercritical extraction at a pressure of 450 atmosphere at 70°C for 5 hr followed by extraction for two hours with supercritical CO 2 modified with ethanol (Hyvarinen et al, ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hosseinian and Beta () also reported that sodium hydroxide or calcium hydroxides are the prominent bases which are employed for liberating SDG. Direct acid hydrolysis of milled flaxseed also reported a higher concentration of secoisolariciresinol (8,566 ± 169 μg/g, 8,571 ± 192 μg/g, respectively) from defatted and full fat flaxseed in comparison to the method in which ethanolic extraction was applied before the acid hydrolysis step which yielded 5,172 ± 49 μg/g and 5,159 ± 83 μg/g, respectively (Sarajlija et al, ). A high level of purity (95%) of SDG was obtained in the process of extraction where the defatting of flaxseed powder was done by pilot‐scale supercritical extraction at a pressure of 450 atmosphere at 70°C for 5 hr followed by extraction for two hours with supercritical CO 2 modified with ethanol (Hyvarinen et al, ).…”
Section: Resultsmentioning
confidence: 97%
“…Zanwar, Hegde, and Bodhankar () carried out extraction based on all these methodologies for the preparation of lignan extract and reported that SDG content came out to be the highest in lignan extract obtained by following the method of Eliasson et al (). In another significant work, a noticeable difference was observed in the extraction yield of secoisolariciresinol when direct acid hydrolysis method was used as compared to ethanol preextraction step from defatted and non‐defatted flaxseed (Sarajlija et al, ). In a significant study by Hyvarinen et al (), ground flaxseed meal yielded active ingredient (SDG) having fairly high purity levels (95%).…”
Section: Introductionmentioning
confidence: 99%
“…There are some factors that make it impossible to find final procedures or protocols to isolate and characterize certain bioactive molecules. This could be due to different parts (tissues) in a plant, many of which will produce quite different compounds, in addition to the diverse chemical structures and physicochemical properties of the bioactive phytochemicals [ 30 ]. Both the selection and the collection of plant materials are considered primary steps to isolate and characterize a bioactive phytochemical.…”
Section: Methods Used For Bioactive Compound Extraction Isolationmentioning
confidence: 99%
“…The selected extracts from in vitro raised L. usitatissimum shoots were mixed with 1 mL (4:1 v/v) of the mixture of pyridine and BSTFA and added with 1% trimethylchlorosilane at 70 °C for 60 min to synthesize trimethylsilyl derivatives of lignans. For precise calibration, standards of SECO and ANHSECO were derivatized in the same pattern according to the method of Sarajlija et al [ 75 ]. The analyzer system consisted of Shimadzu 2010 gas chromatography connected with an auto sampler (AOC-20i) and QP-2010 plus mass selective detector for GC/MS analysis.…”
Section: Methodsmentioning
confidence: 99%